INTEGRAL CONNECTIVITY INDEX APPLIED IN THE SELECTION OF PERMANENT PRESERVATION AREAS PRIORITY TO RECOMPOSITION IN THE MUNICIPALITY OF NOVA MARILANDIA, MATO GROSSO - BRAZIL - Perlandim Ramos, Alexander Webber; Santos Galvanin, Edineia Aparecida dos [UNESP]; Silva Nevesc, Sandra Mara Alves da; Dallacort, Rivanildo (Univ Estado Rio Janeiro, 2022)
The objective of this work was to investigate the degradation of Permanent Preservation Areas to identify forest fragments priority to recomposition in the municipality of Nova Marilandia-Mato Grosso, aiming to contribute, from the data and information generated, in the proposition of actions aimed at maintaining the landscape for the gene flow of the biota. For the definition of the categories of restoration priority, the Integral Connectivity Index was applied in the degraded Permanent Preservation Areas, with its IICflux (measurer of gene/environmental flow possibility) and IICconnector (measurer of node importance as the only connection among other fragments), derived from Graph Theory. In the municipality, the most expressive class is pasture (744.22 km(2)), surpassing the areas of Forest Natural Vegetation (687.23 km(2)), Savannah Formation (311.46 km(2)), Agriculture (157.68 km(2)) and Anthropic Uses (4.21 km(2)). Despite this scenario identified in the context of the municipality, the Permanent Preservation Areas are mostly preserved, and 1,706 fragments to be restored are identified; of these, 1,594 with low priority level, 102 with medium and 10 with high. Therefore, simple management measures such as isolation of degraded Permanent Preservation Areas, favoring fragments of high and medium priority of restoration, can provide opportunities for natural forest regeneration, restoring the function of genetic displacement of the local biota in the landscape without the need for high financial investments.
Keywords: Geotechnologies; Landscape; Functionality; Graph Theory; Environmental Planning